2012
DOI: 10.1103/physrevc.86.044304
|View full text |Cite
|
Sign up to set email alerts
|

Detailed spectroscopy of110Cd: Evidence for weak mixing and the emergence ofγ-soft behavior

Abstract: A study of the β + /EC decay of 110 In into levels of 110 Cd is combined with a reanalysis of data from a previous study of 110 Cd with the (n, n ′ γ) reaction with monoenergetic neutrons. The γγ coincidences from the 110 In decay leads to many new assignments of γ rays observed in the (n, n ′ γ) reaction, permitting the observation of weak low-energy transitions, and setting stringent upper limits on unobserved decay branches. The uncertainties on many of the lifetimes from the (n, n ′ γ) reaction are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
(34 reference statements)
1
34
0
Order By: Relevance
“…Later, the presence of intruder states, due to the 2-particle 4-hole proton excitations near the nominal two-phonon triplet, was included through configuration mixing [7][8][9]. Recently, however, it has been found that this interpretation, based on an anharmonic vibrator model with strong intruder mixing, is not consistent with experimental electromagnetic transition rates [10][11][12][13][14][15]. The confrontation between theory and experiment in the Cd isotopes has sparked a more general debate over the nature of nuclei that are not clearly deformed rotors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the presence of intruder states, due to the 2-particle 4-hole proton excitations near the nominal two-phonon triplet, was included through configuration mixing [7][8][9]. Recently, however, it has been found that this interpretation, based on an anharmonic vibrator model with strong intruder mixing, is not consistent with experimental electromagnetic transition rates [10][11][12][13][14][15]. The confrontation between theory and experiment in the Cd isotopes has sparked a more general debate over the nature of nuclei that are not clearly deformed rotors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The even-even Cd isotopes have long been considered one of the main examples of vibrational behavior. Recently, experimental studies have indicated significant deviations from this behavior, in selected two-and three-phonon states, along the Cd chain (A=108-126) [9,10]. Re-examination of the structure of the midshell Cd isotopes suggests that they may represent ( ) O 6 deformed γ-soft rotors rather than ( ) U 5 spherical vibrators.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, advanced experimental studies have reported significant deviations from this behaviour in selected two-and threephonon states, along the Cd chain (A=108-126) [1][2][3]. These observations have led to claims for the "breakdown of the vibrational motion" in these isotopes and the need for a paradigm shift [1,2]. In the present contribution, we examine an alternative explanation for the structure of the Cd isotopes, in terms of U(5) partial dynamical symmetry (PDS) [4].…”
mentioning
confidence: 99%
“…The Cd isotopes have been traditionally considered to be a prime example of spherical vibrators. Recently, advanced experimental studies have reported significant deviations from this behaviour in selected two-and threephonon states, along the Cd chain (A=108-126) [1][2][3]. These observations have led to claims for the "breakdown of the vibrational motion" in these isotopes and the need for a paradigm shift [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation